The A List : Ali Reynolds #14 - Jance, Judith A. (New York : Gallery Books, 2019)
A threat from her past has Ali Reynolds and her team racing against the clock to stop a ruthless killer.
Keywords: Reynolds, Ali (Fictitious character) -- Fiction; Reynolds, Ali (Fictional character) -- Fiction; Suspense fiction